Knowledge, attitude, and practice of voluntary blood donation among the nursing students of Universiti Malaysia Sabah - M Tanveer Hossain Parash; Sadia Choudhury Shimmi; ABM Tofazzal Hossain (Malaysian Journal of Medicine and Health Sciences, 2020)
The healthy, active, and receptive huge student population is potential blood donors to meet safe blood requirements. The study aimed to assess the current level of knowledge regarding blood donation of nursing students of the Faculty of Medicine & Health Sciences, UMS and to observe their attitude towards voluntary blood donation and to explore their practice as a voluntary blood donor. Methods: This cross-sectional study was conducted from July 2015 to June 2018 among one hundred and eight (108) nursing students who were included in this study by simple random sampling. The researchers explained the study design, objectives, and methodology to the selected subjects and obtained written consent from them. The study assessed the current level of knowledge and observed their attitude towards voluntary blood donation and explored their active involvement in donating blood through a validated questionnaire. Results: There were 89 female and 19 male participants in the study. Almost every student (96%) knew their blood group and most of them were correct about the health status of a blood donor. They had a lack of knowledge regarding the time required for blood donation and the amount of blood collected in each bag. Although most of the students were very favourable to donate blood, only 34% had previous experience of donating blood out of them; only 6% regularly donated voluntarily and on demand. Conclusion: From this finding, it can be recommended that measures for increasing knowledge regarding blood donation should be taken, and that would result in increased blood donation.